Leadership Skills Series #2: General Leadership & Purpose/Values - Jennifer Wert; Matthew Sowcik; Jera Niewoehner-Green (EDIS, 2018)
This second publication in the Leaders Skills Series provides Extension professionals with recommendations on how to utilize short leadership videos under the topics of general leadership and purpose/values as tools to develop specific leadership skills. In particular, these videos focus on everyday leadership, utilizing grit, finding one’s purpose and learning how to feel good about work. This publication introduces four videos that can be accessed online and utilized in a number of learning environments like training or meetings. A brief synopsis, a link to the video, and recommended discussion questions are provided for each video.